Year of the locust : a soldier's diary and the erasure of Palestine's Ottoman past - Tamārī, Salīm (University of California Press, 2011)
This text captures the end of the Ottoman world and a pivotal moment in Palestinian history. In the diaries of Ihsan Hasan al-Turjman (1893-1917), the first ordinary recruit to describe the World War I from the Arab side, we follow the misadventures of an Ottoman soldier stationed in Jerusalem.